2019
DOI: 10.1016/j.neuroimage.2018.11.051
|View full text |Cite
|
Sign up to set email alerts
|

Open-field PET: Simultaneous brain functional imaging and behavioural response measurements in freely moving small animals

Abstract: A comprehensive understanding of how the brain responds to a changing environment requires techniques capable of recording functional outputs at the whole-brain level in response to external stimuli. Positron emission tomography (PET) is an exquisitely sensitive technique for imaging brain function but the need for anaesthesia to avoid motion artefacts precludes concurrent behavioural response studies. Here, we report a technique that combines motion-compensated PET with a robotically-controlled animal enclosu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 44 publications
1
42
0
Order By: Relevance
“…Radial, axial and tangential coordinates in (12) are defined with respect to the radial, axial and tangential directions, which in turn are calculated from the Cartesian coordinates (x c , y c , z c ) of the PSF center. The radial direction has unit vector cos(θ c ) sin(θ c ) 0 , and the tangential direction −sin(θ c ) cos(θ c ) 0 , where θ c = atan(y c /x c ).…”
Section: Image Reconstructionmentioning
confidence: 99%
See 3 more Smart Citations
“…Radial, axial and tangential coordinates in (12) are defined with respect to the radial, axial and tangential directions, which in turn are calculated from the Cartesian coordinates (x c , y c , z c ) of the PSF center. The radial direction has unit vector cos(θ c ) sin(θ c ) 0 , and the tangential direction −sin(θ c ) cos(θ c ) 0 , where θ c = atan(y c /x c ).…”
Section: Image Reconstructionmentioning
confidence: 99%
“…Recently, research has been carried out to perform brain PET scans of awake small animals to circumvent the confounding effect of anesthesia [10]. In addition, in scans of freely moving animals the behavior of the animal can be measured during the PET scan [11], [12]. These methods require to perform rigid motion correction on the PET data to obtain brain reconstructions unaffected by motion.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The approach was further validated using mice, where the authors found that mementine led to a 2.6 larger [ 18 F]FDG uptake on awake animals in comparison to anesthetized animals [245]. Kyme et al [246] further investigated the field of awake-animal imaging by using an automated motion-tracking robot in combination with motion correction approaches and placing a visual marker on the animal's head. The robot performed accurate and responsive movements in order to real-time correct the animal's alignment to the center of the FOV.…”
Section: Quantitative Receptor Imaging In Clinical Translationmentioning
confidence: 99%